2010
DOI: 10.1002/srin.201000008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Isothermal Deformation Conditions on The Mechanical Properties of 22MnB5 HPF Steel

Abstract: In the present study, the aluminized 22MnB5 Hot Press Forming (HPF) steel was deformed isothermally in the temperature range of 600-800 8C. The specimens were deformed with 0%, 10% and 30% engineering strain at a strain rate of 0.5/s. Mechanical stabilization of austenite during phase transformation was observed. The influence of strain rate was also studied. It was found that the martensite transformation was affected by the combined effect of mechanical stabilization and dynamic recovery. The influence of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This phase transformation results in the formation of an untempered lath martensite microstructure with a 1 GPa yield strength (YS) and a 1.5 GPa ultimate tensile strength (UTS). 10) These ultra-high strength properties, make press hardened steel parts ideally suited for antiintrusion parts of passenger vehicles such as B-pillar reinforcements, bumper beams, cross beams and roof rails. 6) The 22MnB5 PHS grade is currently the most widely used material for the production of press hardened parts.…”
Section: Introductionmentioning
confidence: 99%
“…This phase transformation results in the formation of an untempered lath martensite microstructure with a 1 GPa yield strength (YS) and a 1.5 GPa ultimate tensile strength (UTS). 10) These ultra-high strength properties, make press hardened steel parts ideally suited for antiintrusion parts of passenger vehicles such as B-pillar reinforcements, bumper beams, cross beams and roof rails. 6) The 22MnB5 PHS grade is currently the most widely used material for the production of press hardened parts.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, martensitic microstructures, including ferrite and bainite, have been observed in a 22MnB5 steel that is austenitized, strained, and quenched. 22) In this regard, the larger plastic strain or the higher temperature when imposing the plastic strain, the larger the volume fraction of the ferrite. 22) Taking into account that shearing process imposes a strain of over 4.0 on the sheared surface, 23) the literature 22) gives the idea that a large fraction of austenite around the hot-sheared surface transforms to ferrite.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that flow curve of isothermally compressed specimen has a plateau curve and stress is lower than 250 MPa, while the flow curve of simultaneously deformed and quenched specimen has an ascending characteristic and stress value increases up to 500 MPa. High temperature isothermal forming brings the possibility for dislocations and defects which are responsible for strain hardening to annihilate and consequently the forming load is low [14,22]. However, due to continuous temperature decrease during the simultaneous forming and quenching process, defects grow continuously and the increase of forming load is resulted.…”
Section: Flow Curvesmentioning
confidence: 99%
“…During forming, different defects such as dislocations are produced [13]. While during isothermal compression process these defects annihilate due to high temperature, specimens which experience simultaneous forming and quenching processes do not get this opportunity [14]. It is well established that martensitic transformation involves the coordinated movement of atoms [15,16].…”
Section: Hardnessmentioning
confidence: 99%